Trade Adjustment and Human Capital Investments : Evidence from Indian Tariff Reform - Edmonds, Eric.; Pavcnik, Nina.; Topalova, Petia (Washington, D.C. : International Monetary Fund, 2007)
Do the short and medium term adjustment costs associated with trade liberalization influence schooling and child labor decisions? We examine this question in the context of India's 1991 tariff reforms. Overall, in the 1990s, rural India experienced a dramatic increase in schooling and decline in child labor. However, communities that relied heavily on employment in protected industries before liberalization do not experience as large an increase in schooling or decline in child labor. The data suggest that this failure to follow the national trend of increasing schooling and diminishing work is associated with a failure to follow the national trend in poverty reduction. Schooling costs appear to play a large role in this relationship between poverty, schooling, and child labor. Extrapolating from our results, our estimates imply that roughly half of India's rise in schooling and a third of the fall in child labor during the 1990s can be explained by falling poverty and therefore improved capacity to afford schooling.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet